Platelet-derived TGF-β1 is related to portal vein thrombosis in cirrhosis by promoting hypercoagulability and endothelial dysfunction - Jiang, Siyu; Ai, Yingjie; Ni, Liyuan; Wu, Ling; Huang, Xiaoquan; Chen, Shiyao (Frontiers in Cardiovascular Medicine, 2022)
Background Portal vein thrombosis (PVT) is a serious complication of cirrhosis accompanied with unclear pathogenesis. TGF-β has been implicated in atherosclerosis and venous thrombosis whereas study regarding its part in PVT is lacking. The aim of this study was to explore the role of cytokine TGF-β1 in PVT and the potential mechanism. Methods We included patients with cirrhotic gastroesophageal varices and divided them into two groups according to the presence of PVT. Serum levels of TGF-β1, IL-11, CD14, IFN-γ, Fasl, Granzyme B and IL-21 were detected using Cytometric Bead Array kit and compared between two groups. Coagulation status was assessed using thromboelastography (TEG). Endothelial cells were treated with TGF-β1 and evaluated for endothelial dysfunction by RT-PCT. Results Our results uncovered that TGF-β1 (6866.55 vs. 3840.60 pg/ml, P=0.015) significantly increased in PVT group. Other cytokines showed no difference between PVT and non-PVT groups. Besides, TGF-β1 was correlated with PLT, fibrinogen, TEG-CI, TEG-MA and TEG-α (coef=0.733, 0.494, 0.604, 0.608 and 0.511; P <0.001, 0.027, 0.004, 0.004 and 0.021, respectively), which indicated a hypercoagulable state in PVT patients. RT-PCR of liver sinusoidal endothelial cells showed markable increment of vWF, TM, ICAM-1, VEGF after TGF-β1 treatment, suggesting involvement of endothelial dysfunction. Conclusion Elevated TGF-β1 exhibited association with hypercoagulability and promoting effect on endothelial dysfunction, closely related with PVT in cirrhotic patients.